2014
DOI: 10.1590/0103-6440201302438
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Endodontist Posture Utilizing Cinemetry, Surface Electromyography and Ergonomic Checklists

Abstract: The postural risk factors for dentists include the ease of vision in the workplace, cold, vibration and mechanical pressure in tissues, incorrect posture, functional fixity, cognitive requirements and work-related organizational and psychosocial factors. The objective was to analyze the posture of endodontists at the workplace. Eighteen right-handed endodontists aged 25 to 60 years (34±3) participated in the study. Electromyography, kinemetry, ergonomic scales (RULA and Couto's checklist) and biophotogrammetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…Other studies have used evaluation methods or reference postures different from the BHOP (Beach) concept . As an example, RULA and Couto's checklist were used by Onety et al . to assess ergonomics in right‐handed endodontists.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used evaluation methods or reference postures different from the BHOP (Beach) concept . As an example, RULA and Couto's checklist were used by Onety et al . to assess ergonomics in right‐handed endodontists.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies dealing with the physical strain on the dentist during root canal preparation. Onety et al ( 2014 ) found that the muscle groups used in manual root canal preparation differ from those used in mechanical preparation. The study was made in a simulated treatment situation and does not contain any information about the strain the dentists themselves felt when using the different methods.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies dealing with the physical strain on the dentist during root canal preparation. Onety et al found that the muscle groups used in manual root canal preparation differ from those used in mechanical preparation (Onety et al 2014). The study was made in a simulated treatment PeerJ reviewing PDF | (2016:02:9277:1:0:NEW 27 May 2016)…”
Section: Resultsmentioning
confidence: 99%